2018
DOI: 10.1159/000487350
|View full text |Cite
|
Sign up to set email alerts
|

Transient Receptor Potential Vanilloid 4 Activation-Induced Increase in Glycine-Activated Current in Mouse Hippocampal Pyramidal Neurons

Abstract: Background/Aims: Glycine plays an important role in regulating hippocampal inhibitory/ excitatory neurotransmission through activating glycine receptors (GlyRs) and acting as a co-agonist of N-methyl-d-aspartate-type glutamate receptors. Activation of transient receptor potential vanilloid 4 (TRPV4) is reported to inhibit hippocampal A-type γ-aminobutyric acid receptor, a ligand-gated chloride ion channel. GlyRs are also ligand-gated chloride ion channels and this paper aimed to explore whether activation of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 47 publications
2
10
0
Order By: Relevance
“…The inhibition of I K is unlikely due to the decrease in the expression of these three Kv subunits. Previous studies showed that when TRPV4 is chronically or persistently activated, the expression of ion channels and receptors may change [24]. In this study, the hippocampal expression levels of Kv1.2 and Kv2.1 decreased markedly when the mice were injected with GSK1016790A for 3 days (Fig.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…The inhibition of I K is unlikely due to the decrease in the expression of these three Kv subunits. Previous studies showed that when TRPV4 is chronically or persistently activated, the expression of ion channels and receptors may change [24]. In this study, the hippocampal expression levels of Kv1.2 and Kv2.1 decreased markedly when the mice were injected with GSK1016790A for 3 days (Fig.…”
Section: Discussionsupporting
confidence: 50%
“…The protein levels of Kv subunits in vehicle-treated PISE mice and HC-067047-treated PISE mice were normalized to those in vehicle-treated control mice. The concentrations of these drugs were chosen according to previous reports [8,9,24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For patch clamp recording, GSK1016790A, 5,6‐EET, HC‐067047, RN1734, 8‐bromoadenosine 3′,5′‐cyclic monophosphate sodium salt (8‐Br‐cAMP), phorbol 12‐myristate 13‐acetate (PMA), and bisindolylmaleimide II (BIM II) were extracellularly applied, and N‐[2‐(p‐Bromocinnamylamino)ethyl]‐5‐isoquinolinesulfonamide dihydrochloride (H‐89), PKI, D‐Sphingosine, and KN62 were added to the pipette solution. The concentrations of these drugs were chosen according to previous reports (Hong et al, 2016; Li, Qu, et al, 2013; Qi et al., 2018).…”
Section: Methodsmentioning
confidence: 99%